(untitled) (International Current Pharmaceutical Journal, 2014)
Aim of the present study was to identify some phenolic compounds isolated from the dried powder leaves of Solanum Elaeagnifolium Cav. (Solanaceae family) collected from Benghazi area, Libya originally native in the Americas. The extraction was carried out with methanol at room temperature and treated by acidification (H2SO4, pH = 4) & basification (NH4OH, pH = 10). The compounds were separated by chromatographic method through a wet glass silica gel column and purification by medium pressure liquid chromatography (MPLC). The experiment yielded one novel compound named 2-(2-hydroxyphenoxy)-3,6,8-trihydroxy-4H-chromen-4-one [A3] and three previously known phenolic which were isolated for the first time from this plant under study (Quercetin [A1], Rutin [A2] & Mangiferin [A4]). The structures were determined using modern spectroscopic techniques (IR, EI-mass, 1H-NMR, 13C-NMR, APT, HMQC & COSY) using DMSO-d6 solvent in magnetic resonance application. DOI: http://dx.doi.org/10.3329/icpj.v3i3.17890 International Current Pharmaceutical Journal, February 2014, 3(3): 234-239